MYOGLOBIN CONTENT IN CARDIAC MUSCLE OF PHYSICAL EXERCISE INDUCED RAT (Rattus norvegicus) - Rahayu, Sri; Puspitaningrum, Rini; Sadikin, Mohammad (SIMBIOSIS, 2017)
ABSTRACT The research was aimed to analyzing the impact of 7 days arobic exercise in elevating rat cardiac muscle myoglobin. Experimental in vivo study on 20 male Wistar rat induced by 20m/ min treadmill aerobic exercise for 1, 3 and 7 days. Research was done in Animal house and protein laboratory, Biochemistry and Molecular Biology Department, FK UI and laboratory of Biochemistry and Molecular Biology, Biology Department FMIPA UNJ for 10 months. Myoglobin concentration was analyzed by spectrofotometry techique based on myoglobin Soret absorbance in ?503nm.  Myoglobin protein expression was assesed with Western blot technique. Standard curve measurement on myoglobin content with horse myoglobin shown that there was an increase on the absorbance value. The result  showedanthat the standar curve was able to be used as standard curve to calculate myoglobin concentration on cardiac muscle within 503 nm. Spectrophotometry myoglobin concentration measurement on Soret absorbance has shown increasing concentration on myoglobin since the first treatment day. Mean myoglobin concentration value has increased  on the 3 rd and 7 th day, with highest value on the 7 th treatment day (0,0656 ± 0,0001). Western blot analysis showed ng on darker band on treatment group compared   on  to control. When aerobic exercise was given longer, the band shown darker means that myglobin content was higher. Myoglobin concentration can be measured by spectrophotometry on 503 nm. Aerobic physical exercise increased myoglobin on rat cardiac muscle since the first treatment day and  still increase oduring the treatment day. Highest level was shown on the 7 th treatment day. Keywords : myoglobin, cardiac, muscle, exercise, rat
Keywords: myoglobin, cardiac, muscle, exercise, rat